STRATEGIC PRIORITIES OF UKRAINIAN MARITIME TRANSPORT INFRASTRUCTURE DEVELOPMENT MANAGEMENT - Сотниченко, Людмила; Кузьменко, Катерина; Табенський, Сергій (SWorldJournal, 2025)
The approaches for essence uncovering of the definition of "enterprise strategy" are discussed in the article. The key problems of Ukrainian seaports development strategy are substantiated. The main strategic priorities for Ukrainian maritime transport in